Iron-Catalyzed Oxidation of 1-Phenylethanol and Glycerol With Hydrogen Peroxide in Water Medium: Effect of the Nitrogen Ligand on Catalytic Activity and Selectivity - Ros, Dimitri; Gianferrara, Teresa; Crotti, Corrado; Farnetti, Erica (Frontiers in Chemistry, 2020)
The iron(II) complexes [Fe(bpy)3](OTf)2 (bpy = 2,2’-bipyridine; OTf = CF3SO3) (1) and [Fe(bpydeg)3](OTf)2 (bpydeg = N4,N4-bis(2-(2-methoxyethoxy)ethyl)[2,2'-bipyridine]-4,4'-dicarboxamide) (2), the latter being a newly synthesized ligand, were employed as catalyst precursors for the oxidation of 1-phenylethanol with hydrogen peroxide in water, using either microwave or conventional heating. With the same oxidant and medium the oxidation of glycerol was also explored in the presence of 1 and 2, as well as of two similar iron(II) complexes bearing tridentate ligands, i.e. [Fe(terpy)2](OTf)2 (terpy = 2,6-di(2-pyridyl)pyridine) (3) and [Fe(bpa)2](OTf)2 (bpa = bis(2-pyridinylmethyl)amine) (4): in most reactions the major product formed was formic acid, although with careful tuning of the experimental conditions significant amounts of dihydroxyacetone were obtained. Addition of heterocyclic aminoacids (e.g. picolinic acid) increased the reaction yields of most catalytic reactions. The effect of such additives on the evolution of the catalyst precursors was studied by spectroscopic (NMR, UV-visible) and MS techniques.